Characteristics of fractures development and its controlling factors within the buried hill reservoirs from the Archaean metamorphic basement in the Bozhong Sag, Bohai Bay Basin, Eastern China - Wang, Wei; Yi, Jian; Shan, Xuanlong; Zhang, Xintao; Liu, Xiaojian; Liu, Pengcheng; Ren, Shuyue (Frontiers in Earth Science, 2022)
Metamorphic rocks have almost no primary pore space, and their formation of large-scale reservoirs depends on fractures and related secondary pore space formed by tectonic and fluid activities. The BZ19-6 block in the Bozhong Sag, Bohai Bay Basin, is the largest and deepest buried basement condensate field of buried-hill in the world, and its reservoirs are characterized by strong heterogeneity. In this paper, we systematically summarize the characteristics of fracture development, explore the main factors controlling fracture development, establish a fracture development model and clarify the influence of fractures on reservoir quality by using core and microscopic thin section observations, physical property data, imaging logging data and 3D seismic data analysis. The results show that the major types of fractures in the study area are tectonic fractures and dissolution fractures. In particular, the tectonic fractures are widely developed, accounting for 71.7% of the total number of fractures. Migmatization controls the lithological distribution of Archean metamorphic rocks. The migmatitic granite, having the highest degree of migmatization, is the dominant lithology for fracture development because it is rich in brittle minerals, such as feldspar and quartz. Strong compressional orogeny occurred during Indosinian period when many fractures initially developed, which become dominant among the tectonic fractures. Compression-tension-compression multistage tectonic movements characterized the Yanshanian period. During this period, fractures of different degrees formed. The Himalayan period, critical for fracture reconstruction, reactivated the early fractures and promoted the positive influence of atmospheric freshwater and organic acids on fracture reconstruction. Fractures are distributed unevenly in the vertical direction, and fracture-intensive zones are the main development sites for favourable reservoirs because they enhance the porosity and permeability of Archean metamorphic rocks. It means that these fractures can provide effective storage space for oil and gas, which is key for the formation of large-scale reservoirs. In addition, fractures can provide migration channels for organic acids and atmospheric freshwater, which lead to later dissolution, and connect various dispersed dissolution pores to improve the effectiveness of reservoir space.